Características morfológicas y manejo agronómico del pasto Marandú (Brachiaria brizantha) en el Ecuador - Mendoza Vite, José Manuel (2022)
The present research was developed in all agronomic sectors of Ecuador, whose purpose was to determine the effect of cutting age on the morphology, nutrition and productive behavior of Marandú (Brachiaria brizantha cv Marandú); using a randomized complete block design with experimental units, where the taxonomy, and its agronomic management, it was concluded By characterizing the morphology of the According to the effect of cutting age Marandú leaf/stem ratio at 20 days (82.22); At 25 days, number of leaves (2.23) and aerial biomass/root biomass ratio (0.49); finally reached the plants at 30 days Height (66.23 cm). The agricultural performance of Marandú was found to vary as a function of the effect of cutting age as a result of the extrapolation of the following variables: green matter (17.37 and 17.76 t ha-1) and dry matter (3.09 and 3.41 t ha-1). 25 days and 30 days, respectively. In addition, 20 days of mowing affected the chemical composition of the Marandú grass, which had a crude protein content of 14.56% and a crude fiber content of 25.21%.